The Role of Motive in Premeditated Murder - Rukanda, Lalu Muhammad; Harun, Rina Rohayu; Ufran, Ufran (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The motive behind a crime is contingent upon the perpetrator's mens rea, or their inner attitude and intention, to carry out an actus rea, or the actual commission of a wrongful act. This study seeks to offer a comprehensive examination and evaluation of the significance of discerning the purpose as a means for courts to ascertain the underlying circumstances of planned homicide, so enabling judges to render suitable and equitable judgments. This study employs a normative juridical methodology, which centers on doing literature and legislation research with analytical descriptive research parameters. The research findings indicate a lack of comprehensive elucidation on the motives outlined in Article 340 of the Criminal Code. Hence, the utilization of motive is constrained to the principles of law and the personal judgment of the presiding judge in the trial. As there is no analysis of the underlying intention, the Panel of Judges is not obligated to establish a motive for the homicide based on the information presented. Consequently, a range of conclusions were rendered, with some resulting in acquittal and others in conviction, as the judge did not establish any reason for the murder based on the evidence presented. Nevertheless, according to the Indonesian edition of the Criminal Code, Law no. 1 of 2023, the motive mentioned in Article 54 Paragraph (1) Sub B of the Criminal Code must be present prior to the verdict.